PERSEPSI PETANI TERHADAP PENGGUNAAN PUPUK ORGANIK PADA USAHATANI MENDONG - Tenten Tedjaningsih; Suyudi Suyudi; Hendar Nuryaman (Universitas Galuh Ciamis, 2017)
Changing a habit is not an easy job, let alone that has great risks as they relate to social and cultural issues. In understanding of technological innovation requires mental readiness to take the decision to adopt it through a process of perception, because the rate of adoption of an innovation depends on the perceptual characteristics of the adopter of innovation that includes the company telnologi relative advantage, the level of conformance level of complexity, can be tried and can be observed. The purpose of this study to examine the relationship between the characteristics of the farmers, the communication behavior and support efforts by the perception of farmers to use organic fertilizer on crops mendong. Partially, the data were analyzed using Spearman Rank analysis, while simultaneously using Kendall concordance coefficient W. Analysis Research was conducted in February-November 2016 using the method of survey. Sampling using simple random sampling against rushes farmers in Sub Manonjaya with a total sample of 30 farmers.The results showed the internal characteristics of the farmers, support the business climate as well as the perception of farmers on organic farming fertilization mendong included in the medium category and communication behavior are included in the low category. Simultaneously there is a relationship between the internal characteristics of the farmers, the communication behavior and support the business climate by perception of farmers on the use of organic fertilizer to the level of the relationship is very close. Partially that have a relationship with the perception of the use of organic fertilizers is the communication behavior and the support of the business climate. Guidance to the farmers both individually and institutionally still needs to be done to encourage farmers to use organic fertilizer on farm mendong.